THE HISTORY AND ROLE OF "VOICE OF AMERICA” INFLUENCE ON THE COLLAPSE OF THE USSR - Yuldashev Akmal Kurbanbayevich (Journals Park Publishing, 2023)
This article is about the development of the Soviet mass media after 1985 and the growing influence of VOA. Also, information on the political and economic problems of the USSR, Gorbachev's position and his speeches, important press coverage is analyzed. In addition, the results of freedom of the press, such as "Vzglyad", will be discussed.
Keywords: Vzglyad, Lastochka, Media, Vlasov, VOA, Pravda, Copy, live broadcast, self-censored.